2010
DOI: 10.1103/physreva.82.022314
|View full text |Cite
|
Sign up to set email alerts
|

Single-experiment-detectable nonclassical correlation witness

Abstract: Recent progress in theories of quantum information has determined nonclassical correlation defined differently from widely-used entanglement as an important property to evaluate computation and communication with mixed quantum states. We introduce an operational method to detect nonclassical correlation of bipartite systems. In this method, we use particular maps analogous to the well-established entanglement witnesses. Thus, the maps are called nonclassical correlation witness maps. Furthermore, it is proved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 33 publications
2
47
0
1
Order By: Relevance
“…This behavior is not observed for quantum discord explained below. As for nonclassical correlations, among the exiting measures [18,29,31,34,35,36,37,38,39,40], we evaluate quantum discord [18], which has been studied for quantum computing [21,37,41,42] and broadcasting of quantum states [43,44]. The dynamics of quantum discord is also studied [45].…”
Section: Classical/nonclassical Correlationsmentioning
confidence: 99%
“…This behavior is not observed for quantum discord explained below. As for nonclassical correlations, among the exiting measures [18,29,31,34,35,36,37,38,39,40], we evaluate quantum discord [18], which has been studied for quantum computing [21,37,41,42] and broadcasting of quantum states [43,44]. The dynamics of quantum discord is also studied [45].…”
Section: Classical/nonclassical Correlationsmentioning
confidence: 99%
“…Indeed, as was established in a pioneering work by Zurek and Ollivier [17], even separable mixed states can be endowed with correlations exhibiting non-trivial quantum features. In the case of systems consisting of distinguishable parts various measures have been advanced to characterize quantitatively the different ways (besides entanglement) in which quantum correlations can manifest themselves [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Prominent among these are quantum discord and the measures of correlations based upon the disturbances of quantum states due to local measurements proposed by Luo [21][22][23] and by SaiToh and collaborators [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently various methods to detect zero-discord [28][29][30] have been proposed for a given state as well as for an unknown state [31]. Moreover, it is found that vanishing quantum discord is related to the complete positivity of a map [32] and the local broadcasting of quantum correlations [15].…”
Section: Introductionmentioning
confidence: 99%